Digital Tools, Sectoral Dynamics, and Learning Intensity: An Empirical Analysis of KM Adoption Across Industries - Widaningsih; Lestari, Putri Ayu (Commercium : Journal of Business and Management, 2024)
This study examines how the adoption of knowledge management (KM) systems influences organizational learning (OL) outcomes across sectors. In the era of digital transformation, platforms such as Learning Management Systems (LMS), Electronic Performance Support Systems (EPSS), and collaboration tools like Microsoft Teams play a pivotal role in knowledge strategies. The study aims to assess whether the use of these systems is associated with learning intensity, measured by training hours and per-employee spending. A cross sectional analysis was conducted using secondary data from LinkedIn Learning, ATD, Microsoft, and international databases such as OECD and the European Commission. Independent variables included LMS and EPSS/KMS adoption rates, and Microsoft Teams’ user metrics. Dependent variables captured organizational learning outcomes across sectors, including healthcare, manufacturing, and services. Results indicate a positive association between the adoption of LMS and collaboration tools with increased learning intensity. Organizations with high LMS usage and digital collaboration capabilities reported greater training hours and learning investments. EPSS/KMS usage remains limited but represents untapped potential for performance aligned learning. Sectoral differences were notable, with manufacturing leading in training hours, while healthcare focused on compliance learning. Organizational size also influenced outcomes, with larger firms better equipped to support structured learning systems. The findings contribute to understanding how KM systems influence organizational learning performance and highlight the need for context specific KM strategies. Despite some limitations in data scope and causality, the study emphasizes the strategic importance of aligning KM tools with learning goals to foster adaptive, knowledge driven organizations.